Peer association and routine activities in sex worker patronage among male migrant workers - Yang, Xiaozhao Yousef (Deviant behavior, 2022)
Studies of people who buy sex often focus on psychological and personality factors with less attention paid to the role of social contexts. This study integrates the two lines of inquiry, routine activity theory and peer deviance, to examine the social process of paying for sex. We argue that deviant peer association may shape buying sex due to peers’ role in shifts in the three components of routine activity theory: motivation, targets, and lack of guardians. With rich information on sexual behaviors from the China Migrant Sexual Health Survey (n = 1,521), we conducted a series of regressions and structural equation models on commercial sex behaviors among male migrants. Our findings demonstrate that having more peers engaged in deviance is significantly associated with buying sex; the three routine activity components are also significantly associated with buying sex; the peer effect on buying sex is significantly (39% of the variance) mediated by routine activities. These results help understand the role of routine activities in mediating peer association and buying sex, and also contributes to the literature of sex work on the less-studied population of sex work clients in China. Theoretically, the results provide evidence for the role of peers in shaping routine activities.